Morphological and physiological studies of colletrichum spp. - Dorrina Sindun, Ujai. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Fungi of genus Colletotrichum is known worldwide as plant pathogen. The genus causes disease called anthracnose in plants. Seven isolates of Colletotrichum spp. were used in this study. Different species had different colony colour. Of these seven species, only two species produced conidia on malt extract agar (MEA) media after seven days of incubation. Different isolates of the Colletotrichum spp. had different optimum temperature and pH to grow. All the seven isolates of the Colletotrichum spp. indicated the optimum growth temperature at between 25°C-30°C. Five species revealed the optimum growth in acidic condition, between pH 4.5-pH 6.0. One species showed its optimum growth at pH 7.0 and another species showed optimum growth in weak alkaline condition, pH 8.0.